The role of parents’ education level in moderating the relationship between primary students' reading self-efficacy and reading comprehension - Wan Norudin, Siti Wan Aminah; Che Hassan, Norlizah; Mohamed Mokhtar, Marzni; Yasin, Maizura; Ramli, Mohd Shahridwan (Human Resource Management Academic Research Society, 2024)
Mastery of reading comprehension is crucial for academic success, as it enables students to effectively learn and understand material in all subjects. This study investigates level of parents’ education as moderator between students' reading self-efficacy and reading comprehension. This study involved 393 fifth-grade students and their parents from fifteen primary schools in Kelantan, Malaysia. Participants were chosen through a multi-level random sampling method. The results of the study include both descriptive testing and inferential analysis utilizing structural equation modelling. Given that both parents' educational levels have significant regression coefficients, the study results suggest to a partial moderator effect, indicating that students' reading self-efficacy on reading comprehension relies on both parents' educational levels. A more thorough understanding of how students' reading self-efficacy affects reading comprehension differently according to their parents' education levels may help stakeholders in education including policy makers, school administrators, and teachers in developing more effective and comprehensive educational programs for students.